Barriers to Strategic Plan Implementation: An Explorative Study of Manufacturing Sector Organisations in Sri Lanka - Kariyapperuma, Seshika Kithmini (Technium Social Sciences Journal, 2025)
The main concern for every strategic-level manager is to enable the best performance through effective planning and successful implementation of strategies to gain competitive advantages over their competitors. However, formulating new strategies and executing those strategies throughout the organisation are challenging tasks. Without effective implementation, no organisational strategy can succeed. Thus, this research explored the barriers to implementing strategies at manufacturing sector organisations in Sri Lanka. A qualitative research method was used to collect data from 18 managers of six manufacturing sector organisations, using the purposeful sampling technique. The semi-structured interview method was used, and the collected data were analysed using Thematic Analysis Technique. It was found that barriers to the effective implementation of a strategy exist both inside and outside the selected organisations. Five distinct barriers were identified: poor strategy formulation, inadequate resources for implementation, managerial issues, organisational cultural barriers, and external environmental barriers. This study contributes to an explanation of why so many strategy implementation efforts fail. It is one of the few papers addressing the strategic issues of Sri Lankan manufacturing sector organisations. Finally, recommendations to eliminate the identified barriers were provided to managers of the selected organisations.